COVID in Context: The Lived Experience of Richmond's Low-Income Older Adults. (9th February 2022) - Winship, Jodi M.; Gendron, Tracey; Waters, Leland; Chung, Jane; Battle, Kimberly; Cisewski, Melissa; Gregory, Melody; Sargent, Lana; Zanjani, Faika; Slattum, Patrica; Mackiewicz, Marissa; Diallo, Ana; et al.
Taking a phenomenological approach, this qualitative study describes the lived experiences of low-income older adults during the COVID-19 pandemic. A socio-ecological model was used to organize the five identified themes describing the lived experience: socio-economic context, Black Lives Matter and the politics of race, COVID and polarized views of COVID, interpersonal context (social connections), and individual context (feelings, beliefs, and behaviors). Study findings illustrate the intersectionality of contextual influences on the experience of low-income older adults. Study participants demonstrated remarkable resilience and coping strategies developed in response to the challenges they experienced throughout their lifetime which benefited them when faced with the pandemic, social unrest, and political events that took place in 2020. This study highlights the importance of understanding the larger context of COVID-19 which has significant implications for policy makers and public health leaders.